Level of Regional Financial Independencein the Eastern Region of Indonesia: Regional Original Income, Employee Expendituresand Capital Expenditures - Muhamad Ashari; Junaedy (Faculty of Business and Economics , Universitas Yapis Papua, 2023)
Regional financial independence is an indicator of a region's ability to carry out regional activities independently without depending on other parties. Regional financial independence is generally influenced by several factors. One factor of independence is Regional Original Income. This research aims to examine the influence of Regional Original Income, employee expenditure, and capital expenditure on the level of regional financial independence. The research method used is quantitative replication research with multiple linear regression analysis as the analysis method. The research sample was 65 consisting of 17 regions with 5 (five) years of observation. The research results show that local revenue and employee expenditure influence the level of regional financial independence, while capital expenditure does not have a significant influence on the level of regional financial independence.